Fatores associados ao sobrepeso e obesidade em adolescentes do município de Fernandópolis-São Paulo - Vidotti, Ângela Maria Buosi (2008)
The prevalence of overweight and obesity has had a considerable increase on the last decades, becoming one of the main public health problems. The excess of weight in adolescents is alarming due to the much increased risk of its persistence up to adult ages as well as the risks of associated diseases. The aim of this work is to evaluate the nutritional state of adolescent students of elementary degrees in private and public schools in Fernandópolis – SP to get to know overweight and obesity, investigating possible associations with socioeconomic factors, energy expenditure and food habits on the determination of excess of weight. Evaluations were made on 94 students, being 70 female (74%) and 24 male (26%), aged from 10 up to 15 years old, enrolled in the elementary school in public and private institutions in the county of Fernandópolis. The nutritional state was assessed through BMI /age/sex, according to Frisancho classification. It was verified that 49 individuals (52%) are eutrophic; 6 individuals (6%) are underweighted, 11 individuals (12%) are at risk of underweight, 17 individuals (18%) are with overweight and 11 individuals (12%) are obese. These data match the results found in Brasil, approximating the maximum found levels. The level of education of the family provider was positively associated to the prevalence of obesity and overweight, once 57% from the 28 individuals with this diagnostic mentioned the provider had a graduation in higher education. Among adolescents assessed with overweigh or obesity, 93% live in residences with up to four people and 7% live in residences with five or more people; hence the fact of living in residences with up to 4 people can be related to the prevalence of overweight and obesity. The preference about free time occupation denotes tendency to activities that demand less energy expenditure like watching TV, video game and computer instead of activities like playing on the street or sports practice. The omission of meals is a frequent habit of adolescents, mainly the breakfast, which is not taken by 26% of the interviewees. During the scholar break, adolescents relate preference for baked snacks, but frequently accompanied by soft drinks or artificial drinks and fruit was rarely mentioned. Analyzing the frequency of meals, it is possible to note that the assessed population consumes the necessary food for the age, though still consumes food with low nutritional level and high caloric level. In the face of the excess of weight of population, the preference for low energy expenditure activities and inappropriate food consumption, it becomes clear the need of developing strategical plans of appropriate intervention. Keywords: nutritional state, adolescents, food habits, overweight, obesity.